PENGEMBANGAN APLIKASI BERBASIS WEB TERAPI UNTUK PENYEDIAAN INFORMASI PELAYANAN OBAT DI KOTA PALU: TERAPI WEB-BASED APPLICATION DEVELOPMENT FOR DRUG SERVICES INFORMATION PROVISION IN PALU CITY - Hardani, Muhammad Fakhrul; Hardani, Ririen; M. Zain Gifary; M. Ilham (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Advancements in technology have been widely adopted across industries, including pharmaceutical services. Numerous online pharmacies have emerged, offering convenience to consumers but unfortunately, to some extent, diminished the role of pharmacists. This study aims to develop a web-based application called TERAPI, an online pharmacy that does not reduce the role of pharmacists. The work includes designing the operational configuration, and the user interface. The development utilizes technologies like Google Sites, third-party applications, embedded code, and artificial intelligence. The process includes programming validation, menu layouting, and database creation.TERAPI provides six features: Drug, Pharmacy, Consultation, Hospital, ICU, and Order. There are six different test cases (TC): TC A01 verifies dashboard accessibility, TC B01 and B02 indicate that users with valid credentials can create an account (Sign Up), and get into the application (Log In). TC C01, C02, and C03 verify the accessibility of menus Drug, Pharmacy, and Consultation. This application follows the standards and regulations of online drug distribution and does not provide prescription and psychotropic drugs due to safety reasons. Keywords: Application, drugs, pharmacy, service, web